IMPROVING YOUNG LEARNERS’ LISTENING SKILL BY USING NURSERY RHYMES SONG - Putri, Aprilia Riyana (Institut Agama Islam Negeri Kudus, 2018)
Listening is one of the most important skill in learning language for young learners, because the first way to learn language start from learning how to listen. In learning English, most of young learners in Indonesia found some difficulties to listen directly from the native speaker or from the environment, such as from young learners’ school or from young learners’ family, it happened because English is still as the second language in Indonesia which is not use in daily life. Many media uses by most of schools in Indonesia to improve young leraners’ competencies in English, for example by using some application from smartphone or by using song. Here, the researchers choose nursery rhymes song as an alternative media in improving young learners’ listening skill. The experimental research design was employed. The experimental group was taught using nursery rhymes song while the control group was taught using the conventional method. There are two classes in the same level at six grade level from SDUT BUMI KARTINI JEPARA participated in this study, they are from maroco and mesir class. The findings indicated that nursery rhymes song significantly improved the students’ listening skill toward learning English. This study concluded that nursery rhymes song is one of media that is very effective for improving young learners’ listening skill because young learners are very happy to learn English while singing the nursery rhymes song.